Determining the Temporal and Spatial Effects of Human Induced Interventions on Some Water Quality Parameters of Murgul Creek - Şenol Osmanaoğlu; Mehmet Özalp (Doğal Afetler ve Çevre Dergisi)
It is known that human-induced damaging factors on the quality and quantity of water produced by river watersheds cause some negative consequences (pollution, changes in water regime, decreases in flow rate, etc.). Murgul Creek consists of such factors as well, including open pit mining works, multiple run-of-river hydroelectric power plants (RoR-HEPP), new road constructions and expansion of residential areas within its borders. From this point of view, in this research, the aim was to reveal scientific data -both temporal and spatial- on the status of water quality, flow regime and the amount of suspended particles in Murgul Creek caused by these activities. For this purpose, water temperature, pH, electrical conductivity (EC), salinity, total dissolved matter (TDM), dissolved oxygen (DO), nitrate nitrogen (NO3-N) and ammonium nitrogen (NH4-N) parameters were measured monthly for one year at 12 sampling points along the Murgul Creek. In addition, besides determining the amount of suspended solid particles (SSP) and monthly flow rates, analyses were made for arsenic (As), cadmium (Cd), copper (Cu), iron (Fe), lead (Pb) and zinc (Zn) in water samples for a possible heavy metal pollution caused by mining activities. When the results were evaluated, the values of conductivity (438.82 μS/cm), salinity (0.30 mg/L), TDM (400.25 mg/L), NH4-N (0.19 mg/L) NO3-N (5.20 mg/L) and SSP (143.69 mg/L) in water samples close to the mining activities were found to be statistically higher compared to sampling points near the natural and residential areas. In addition, it was determined that Cu (5669 µg/L), Fe (4647 µg/L), Pb (43 µg/L) and Zn (2837 µg/L) values measured in the creek water were statistically the highest at the M5 measurement point at the exit of the mining site.